CIVED (Journal of Civil Engineering & Vocational Education) ISSN 2302-3341 SK DEKAN FAKULTAS TEKNIK No. 0560/UN35.2/KP/2018 - CIVED (Journal of Civil Engineering & Vo SK DEKAN FAKULTAS TEKNIK No. 0560/UN35.2/KP/2018 (CIVED, 2018)
CIVED(Journal of Civil Engineering & Vocational Education)ISSN 2302-3341SK DEKAN FAKULTAS TEKNIKNo. 0560/UN35.2/KP/2018 Penanggung JawabDekan Fakultas Teknik UNP PadangDr. Fahmi Rizal, M.Pd, MT Pimpinan UmumKetua Jurusan Teknik SipilDr. Rijal Abdullah, MT Pimpinan RedaksiRusnardi Rahmat Putra, Ph.D., Eng Sekretaris/BendaharaFaisal Ashar, ST, MT Dewan Redaksi Dr. M. Giatman, MSIEDr. Nurhasan Syah, M.PdDr. Fahmi Rizal, M.PdDr. Indrati Kusumaningrum, M.PdDrs. Revian Body, MSADrs. Juniman Silalahi, M.PdOktaviani, ST., MTFitra Rifwan, S.Pd, MTYuwalitas Gusmareta, S.Pd, M.Pd.TProf. Dr. Slamet Triono Ahmad, M.EdAdrin Thohari, Ph.DDr. Nur Qudus, MTDr. Azwar Inra, M.Pd Redaksi PelaksanaAdetiyawarman Nazwar, Amd Nadra Mutiara Sari, S.Pd., M.EngNova Maulana, S.IP Alamat Redaksi :Jurusan Teknik SipilFakultas Teknik UNP PadangJl. Prof. Dr. Hamka, Air Tawar Padang, 25131Telp. (0751) 7059996